Design energy simulation for architects : guide to 3D graphics - Anderson, Kjell (2014)
"Energy modeling calculations for urban, complex buildings are most effective during the early design phase. And most analysis takes only four to sixteen hours to get results you can use. This software-agnostic book, which is intended for you to use as a professional architect, shows you how to reduce the energy use of all buildings. Written by a practicing architect who specializes in energy modeling, the book includes case studies of net-zero buildings, of Living Building Challenge-certified buildings, as well as of projects with less lofty goals to demonstrate how energy simulation has helped designers make early decisions. Within each case study, author Kjell Anderson mentions the software used and other software that could have been used to get similar results so that you learn general concepts without being tied to particular programs. Each chapter builds on the theory from previous chapters, includes a summary of concept-level hand calculations (if applicable), and gives comprehensive explanations with examples. Topics covered include comfort, design energy simulation, climate analysis, master planning, conceptual design, design development, and existing buildings so that you can create more responsive designs quicker"--
Includes bibliographical references and index.
Keywords: Sustainable buildings -- Design and construction -- Data processing; Architecture and energy conservation; Buildings -- Energy conservation -- Computer simulation; Three-dimensional display systems; ARCHITECTURE / Sustainability & Green Design; ARCHITECTURE / Design, Drafting, Drawing & Presentation; ARCHITECTURE / Methods & Materials